The Effective School Administration Model in Accordance with the “One District, One Quality School” Policy under the Secondary Educational Service Area Office Phayao - Techoweerakul, Kwannapa; Pangthai, Sasirada; Maneewong, Somjai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to: (1) examine the components and current conditions of effective school administration under the “One District One Quality School” policy in schools under the Secondary Educational Service Area Office Phayao; (2) develop a model of effective school administration aligned with the policy; and (3) evaluate the appropriateness and feasibility of the developed model. A mixed-methods research design was employed, guided by the quality management framework of the PDCA (Plan–Do–Check–Act) cycle integrated with the Ministry of Education’s “One District One Quality School” policy. The research setting comprised schools under the Secondary Educational Service Area Office Phayao. Key informants for the interviews included nine participants selected through purposive sampling. The sample used to validate the model components and evaluate its appropriateness and feasibility consisted of 255 participants, including educational administrators, school administrators, and teachers, selected through simple random sampling. Research instruments included an interview form, questionnaire, focus group discussion guidelines, and an evaluation form. Data were analyzed using mean, standard deviation, and descriptive content analysis. The findings revealed that: 1) Effective school administration consisted of five key components: infrastructure and student support systems, school administrators, teachers and educational personnel, administrative management, learning management, and students. 2) the developed administrative model comprised five main elements—principles, objectives, operational processes, evaluation, and success conditions—implemented through the IAMLS mechanism under the PDCA cycle. 3) The evaluation results revealed that the proposed model achieved the highest level of appropriateness and feasibility. This study contributes to the body of knowledge by proposing the IAMLS Model, an effective school administration framework that integrates system theory, the PDCA cycle, and the CIPP evaluation model in a practical manner. The model provides a systematic guideline for improving and strengthening schools under the “One District One Quality School” policy, particularly in promoting systematic management, stakeholder participation, and sustainable improvement in student quality.